Curriculum and design analysis of a mathematics-based educational television program: a case study of Cyberchase animated television series. - Yusop, F.D. (2013)
This paper presents a curriculum and design analyses of an Emmy-award winning children educational television series, Cyberchase. Using Posner’s (2004) four process of curriculum analysis framework, this paper addresses each of the components and relates it to the design principles undertaken by the Cyberchase production team. Media and document analysis techniques were used to examine selected samples of the series. Findings indicate that the series succeed in teaching mathematical concepts, generate interest in mathematics learning and assist in development of mathematical problem-solving skills. This paper may provide information on how the series effectively used multimedia elements to deliver serious academic content in the most entertaining ways.